The Effect Of Shortening The Difference Catches Gill Net Fishing Gear - Yanto, Nofri; Syofyan, Irwandy; Brown, Arthur (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study conducted in May 2015 in the Village Teluk Air, District ofKarimun, Tanjung Balai Karimun Regency , Riau Island Provincial. The aim ofthis study was to determine the effect of shortening of the catches of gill netfishing gear. It is known from research that the shortening gill nets with 20% ofthe catch as much as 95,5 kg, which comprised 246 fishs. By way of fishcaught most dominant snagged. On gill net fishing gear that uses 30%shortening overall number of catches as much as 82 kg, comprising 186 fishs.By way of the most dominant fish caught in etangled. Results of t-test at 95%confidance level showed no effect of shortening of the catches in gill netfishing gear.Key word: Gill net fishing gear, Shortening